2022
DOI: 10.9734/ijecc/2022/v12i121458
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Garlic Genotypes for Resistant Sources against Purple Blotch Disease

Abstract: Garlic is an herbaceous annual bulbous plant in the family Amaryllidaceae grown for its pungent and edible bulb. Among the various biotic factors hindering production and productivity, purple blotch plays a predominant role in changing the crops morpho-physiological characters, thus deteriorating the metabolic activity in turn affecting the yield considerably. Fungicides have been recommended for the control of the disease, however use of fungicides is expensive and not eco-friendly. The best approach to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In favorable conditions, an epidemic may cause the total depression of the crop. High losses were recorded due to purple blotch disease by Vijaykumar et al, (2022) as well as that in onion seed crop has been reported to reach 97% infection Nanda et al, (2016). Irrigation as an agricultural practice can be an important and necessary tool for global food production.…”
Section: Introductionmentioning
confidence: 99%
“…In favorable conditions, an epidemic may cause the total depression of the crop. High losses were recorded due to purple blotch disease by Vijaykumar et al, (2022) as well as that in onion seed crop has been reported to reach 97% infection Nanda et al, (2016). Irrigation as an agricultural practice can be an important and necessary tool for global food production.…”
Section: Introductionmentioning
confidence: 99%